Differential diagnosis between dementia and psychiatric disorders: Diagnostic criteria and supplementary exams Recommendations of the Scientific Department of Cognitive Neurology and Aging of the Brazilian Academy of Neurology - Bottino, Cássio M.c.; Pádua, Analuiza Camozzato De; Smid, Jerusa; Areza-fegyveres, Renata; Novaretti, Tânia [UNESP]; Bahia, Valeria S. (Associação de Neurologia Cognitiva e do Comportamento, 2011)
In 2005, the Scientific Department of Cognitive Neurology and Aging of the Brazilian Academy of Neurology published recommendations for the diagnosis of Alzheimer's disease These recommendations were updated following a review of evidence retrieved from national and international studies held on PUBMED, SCIELO and LILACS medical databases. The main aims of this review article are as follows: 1) to present the evidence found on Brazilian (LILACS, SCIELO) and International (MEDLINE) databases from articles published up to May 2011, on the differential diagnosis of these psychiatric disorders and dementia, with special focus on Dementia due to Alzheimer's and vascular dementia, including a review of supplementary exams which may facilitate the diagnostic process; and 2) to propose recommendations for use by clinicians and researchers involved in diagnosing patients with dementia. Differential diagnosis between dementia and other neuropsychiatric disorders should always include assessments for depression, delirium, and use of psychoactive substances, as well as investigate the use of benzodiazepines, anti-epileptics and pattern of alcohol consumption.

Em 2005, o Departamento Científico de Neurologia Cognitiva e do Envelhecimento da ABN publicou as recomendações para o diagnóstico da Doença de Alzheimer. Essas recomendações foram revisadas através de buscas em bases de dados PUBMED, SCIELO e LILACS, buscando evidências nacionais e internacionais sobre esses temas. Este artigo de revisão tem como objetivos: 1) apresentar as evidências encontradas em bases de dados brasileiras (LILACS, SCIELO) e internacionais (MEDLINE), até maio de 2011, sobre o diagnóstico diferencial desses transtornos psiquiátricos com demência, tendo como foco especial a demência de Alzheimer e a demência vascular, incluindo os exames complementares que podem auxiliar neste processo diagnóstico; e 2) propor recomendações que podem ser úteis a clínicos e pesquisadores envolvidos com o diagnóstico de pacientes com demência. O diagnóstico diferencial entre demência e outros transtornos neuropsiquiátricos deve sempre incluir a avaliação de depressão, delirium, e o uso de substâncias psicoativas, tais como benzodiazepínicos, antiepilépticos e o padrão de consumo de bebidas alcoólicas.
Diagnóstico diferencial entre demência e transtornos psiquiátricos: critérios diagnósticos e exames complementares. Recomendações do Departamento Científico de Neurologia Cognitiva e do Envelhecimento da Academia Brasileira de Neurologia
Keywords: dementia; Alzheimer's disease; depression; alcohol; psychoactive drug; guidelines; consensus; Brazil.; demência; doença de Alzheimer; depressão; álcool; substâncias psicoativas; diretrizes; consenso; Brasil.